Psychological outcomes affect functional outcomes in patients with severe pelvic ring fractures. Issue 10 (October 2021) - Martin, Murphy P; Rojas, David; Dean, Chase S; Lockwood, Winthrop; Nadeau, Jason; Maertens, Andrew; Parry, Joshua; Maher, Michael; Funk, August; Stacey, Stephen; Burlew, Clay Cothren; Mauffrey, Cyril
Highlights: A post-traumatic collaborative team approach is essential to optimize patients' recovery and overall outcomes. Prompt identification and management of patients at risk for developing psychological complications can improve functional outcomes. Specific strategies to address post-traumatic psychological complications in severely injured patients are an important topic for research. ABSTRACT: Purpose: To evaluate the correlation between post-traumatic functional and psychological outcomes in patients with severe pelvic ring injuries. Methods: Forty-four patients who sustained a completely unstable pelvic ring injury (Tile C, AO/OTA 61C) treated in our institution from 2012 to 2017 were included. A telephone interview was performed in 16 of 44 patients to evaluate pelvic functionality, using the Majeed pelvic score, and psychological evaluation, using Hamilton anxiety and depression rating scales. Results: The mean Injury Severity Score (ISS) was 27 ± 12, and mean GCS at presentation was 13 ± 4. Average time from trauma to interview was 3 years (range, 1–5 years). Mean Majeed pelvic score was 67 ± 22. Majeed sub-scores were pain 19 ± 9, work 10 ± 7, sitting 8 ± 2, sexual intercourse 3 ± 2, walking aids 11 ± 2, gait unaided 9 ± 2, walking distance 8 ± 3. Mean depression and anxiety scores were 16 ± 12 and 17 ± 14, respectively. Significant correlations were observed between functional and psychological outcomes ( P < 0.005). Majeed score was negatively correlated with depressive symptoms ( r = -0.721, P = 0.002) and anxiety symptoms ( r = -0.756, P = 0.001). Depression and anxiety scores were positively correlated ( r = 0.945, P < 0.001). Conclusion: Lower functional outcomes in patients with Tile C pelvic injuries were correlated with more severe symptoms of depression and anxiety. We recommend that providers consider and treat patients' mental health condition during posttraumatic recovery.